A coverage strategy for wireless sensor networks in a three–dimensional environment. (20th March 2014) - Feng, Lin; Qiu, Tie; Sun, Zhenlong; Xia, Feng; Zhou, Yu
Coverage is one of the fundamental issues in wireless sensor networks (WSNs). The detection area is non–ideal and the terrain of the detection area is more complex in applications of three–dimensional sensor networks. Consequently, many of the existing coverage strategies cannot be directly applied to three–dimensional spaces. This paper presents a new coverage strategy for the three–dimensional sensor networks. Sensor nodes are uniformly distributed. The cost factor is utilised to construct the perceived probability and the classical watershed algorithm after the transformation of points from the three–dimensional space to the two–dimensional plane using the dimensionality reduction method, which can maintain the topology characteristic of the non–linear terrain. The detection probability in the optimal breath path is used as the measure to evaluate the coverage. Simulation results indicate that the proposed strategy can determine the coverage with fewer nodes, while achieving the coverage requirements of the networks.